3
$\begingroup$

What is solution of the differential equation:

\begin{aligned}x({yy'' + y'^2}) + yy' = 0\end{aligned}

What i am confused about it is the treatment of $$\left(\dfrac{dy}{dx}\right)^2$$ for solving this question. The given answer is \begin{aligned}ax^2 + by^2 = C\end{aligned}

$\endgroup$
6
$\begingroup$

A start: Let $u=yy'$. Then $x\frac{du}{dx}+u=0$.

I expect you can finish from here.

$\endgroup$
  • $\begingroup$ Clever substitution. (+1) $\endgroup$ – user71352 Aug 9 '14 at 5:54
  • $\begingroup$ the solution comes out as\begin{aligned}u=\frac{c_1}{x}\end{aligned} \begin{aligned}\implies yy'=\frac{c_1}{x}\end{aligned} \begin{aligned}\implies ydy=\frac{c_1}{x}dx\end{aligned} on integrating further we get, \begin{aligned}\implies \frac{y^2}{2}=c_1lnx+C\end{aligned} how does it take the exact form of answer that is given? $\endgroup$ – Ritu Aug 9 '14 at 5:58
  • $\begingroup$ $\log|u| = -\log|x| + C \implies |u| = \frac{K}{|x|}$, not $K|x|$. $\endgroup$ – achille hui Aug 10 '14 at 1:10
2
$\begingroup$

Note that:

Given $$y^2$$

If we take the first derivative by implicit differentiation we get

$$2yy'$$

Again taking a derivative we get

$$2(y')^2 + 2y''$$

This leads us to guess $u = y^2$ is a wise substitution.

From it the equation becomes

$$\frac{1}{2}(xu'') + \frac{1}{2}u' = 0$$

Now we divide out the 1/2 and make another substitution $u' = w$ to obtain:

$$xw' + w = 0$$

You can take it from here, once solved go backwards through the chain of substitutions

$\endgroup$
1
$\begingroup$

I took a different approach and got the same answer as those given above. Since $$ x(yy''+y'^2)+yy'=0 $$is equivalent to $$ x\frac{d}{dx}(yy')=-yy' $$or $$ \frac{\frac{d}{dx}(yy')}{yy'}=-\frac{1}{x} $$then $$ \frac{d}{dx}ln(yy')=-\frac{1}{x} $$This integrates to give $$ ln(yy')=ln(x^{-1})+lnC_1 $$which simplifies to $$ yy'=\frac{C_1}{x} $$From here I used a Lie group $G(x,y)=(\lambda x,\lambda^\beta y), \lambda_o=1$ with stabilizers $\mu=\frac{y}{x^\beta}$ and $\nu=\frac{y'}{x^{\beta -1}}$ to rewrite the equation.
$$ \lambda^\beta y \lambda^{\beta -1} y'=\frac{C_1}{\lambda x} $$For the $\lambda$ terms to cancel out, $\beta =0$. Therefore, the first two nontrivial group stabilizers are $\mu=y$ and $\nu=xy'$. Rewriting the ODE in terms of its stabilizers, $$ \nu=\frac{C_1}{\mu} $$Since $$ x\frac{d\mu}{dx}=\nu=\frac{C_1}{\mu} $$we have $$ \frac{\mu ^2}{2}=C_1ln(x)+C_2 $$Allowing the constants to absorb the factor of two and remembering that $\mu=y$, $$ y=\sqrt{C_1ln(x)+C_2} $$There's nothing original about this solution, but I thought you might enjoy seeing an alternate approach to the problem itself. I picked up the Lie theory in Oak Ridge, and since so few people have ever seen it I like to share it when I can.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.